Digital Sociological Review of KP2C in the Use of Whatsapp Groups for Flood Mitigation - Faiz Sarvianto, Dwiki; Kolopaking, Lala M.; Hapsari, Dwi Retno (Sodality: Jurnal Sosiologi Pedesaan, 2022)
KP2C has implemented a flood early warning system through Whatsapp groups since 2016. However, in the areas of Bojong Kulur and Jatirasa, which are the focus of KP2C information and downstream of the Cileungsi and Cikeas rivers, there are still losses for members. The interaction illustrates that achievement of KP2C’s goals has not been maximized, so the meaning of effectiveness is important to explored sociologically with variables thought to be related to it such as the digital divide, social structure’s form, and social capital’s level. This study uses a postpositivism paradigma and survey methods with data qualitative as a support. Respondents in this study were obtained by purposive technique with 40 individuals in RW 24 Bojong Kulur and RW 8 Jatirasa Village as affected areas. The results showed the majority of all variables were dominated by the medium category. Digital divide variable is strongly and positively related to social structure. Both are simultaneously also related to social capital. Therefore, it can be said that if the role of the early warning system is to be effective, then the three variables must clearly be considered.